Radio and infrared study of the supernova remnant candidate HESS J1912+101 - Duvidovich, Laura Patricia (2023)
Aims. We provide new insights into the γ-ray emission from HESS J1912+101, a TeV supernova remnant candidate probably associated with the radio pulsar PSR J1913+1011. Methods. We obtained new observations at 1.5 GHz using the VLA in the D configuration, with the purpose of detecting the radio shell of the putative remnant. In addition, we observed a single pointing at 6.0 GHz toward PSR J1913+1011 to look for a radio pulsar wind nebula. We also studied the properties of the surrounding interstellar medium using data of the 13CO, HI, and infrared emissions, obtained from public surveys. Results. We do not find evidence of a radio shell down to the sensitivity of the new image at 1.5 GHz. We detect faint diffuse emission around PSR J1913+1011 at 6.0 GHz, which could represent a radio pulsar wind nebula powered by the pulsar. We find dense ambient gas at ~60 km s-1, which shows a good spatial correspondence with the TeV emission only in the western and eastern directions. There is also dense gas near the center of HESS J1912+101, where the TeV emission is weak. Using infrared data, we identify an active star-forming region in the western part of the shell. Conclusions. Based on the poor spatial match between the ambient gas and the TeV emission (which shows a good correlation in the western and eastern directions and an anticorrelation in the other directions), we conclude that the hadronic mechanism alone does not give a satisfactory explanation of the γ rays from HESS J1912+101. Additional contributions may come from leptonic processes in the shell of the supernova remnant, together with contributions from PSR J1913+1011 and its pulsar wind nebula and/or from the star-forming region. A confident determination of the distance to the putative remnant is necessary to determine whether these sources are associated or just appear superimposed in the line of sight.